Development of instruments for implementation analysis and effectiveness evaluation of clinical pharmacy services as well as need identification of Telepharmacy services - Rachmawati Felani; Andrajati, Retnosari; Syafhan, Nadia Farhanah; Wispriyono, Bambang (Edelweiss Applied Science and Technology, 2025)
Pharmaceutical services are activities designed to improve the quality of patients’ lives. To measure their effectiveness, four indicators are often used, including input, process, results, and productivity. The purpose of this study is to develop instruments for implementation analysis and effectiveness evaluation of clinical pharmacy services, as well as to identify the needs of telepharmacy services. The study procedures were carried out using qualitative and quantitative methods. The stages of development included literature study, expert panel, validity and reliability testing, and instrument testing. The results showed that at the expert panel stage, using CVR-Lawshe analysis, all question items in instruments 1 and 2 were valid with a CVR value greater than 0.56. Based on the i-CVI values, which were greater than 0.80, all question items were relevant to the study objectives and had high validity. At the validity and reliability testing stage, the Alpha Cronbach values of instrument 2 on compliance and appropriateness of drug use were 0.709 and 0.866, respectively. Meanwhile, the Alpha Cronbach value of instrument 3 was 0.951. At the trial stage, respondents’ understanding of the questions was assessed without any direction. All instruments developed in this study were valid, reliable, and could be effectively applied.